2010
DOI: 10.1111/j.1440-1770.2010.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solar UV‐B exclusion on the phytoplankton community in a sub‐tropical mountain reservoir: a mesocosm study

Abstract: A mesocosm experiment was conducted over a 4 week period to investigate the response of a phytoplankton community in a mountain freshwater reservoir to solar UV-B exclusion. The mesocosms were filled with water taken from the depth of 0.30 m in the reservoir, and exposed to near-ambient solar UV-B (+UV-B) and solar UV-B exclusion ()UV-B). The resulting chlorophyll-a (Chl-a), carotenoids, soluble sugars, algal composition and algal abundance were analysed. The study results indicated that carotenoids, carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Loss of Chl is a negative effect of UV-B and may be an indication of ongoing senescence (Weichmann 2000). Many reports have shown that one of the most common symptoms of elevated UV-B exposure is a decrease in Chl concentration (Medina et al 2010, Zu et al 2011. Declines in Chl concentration in UV-B treated shoots have been related to the suppression of aminolevulinic acid synthesis or a reduction in protochlorophyllide (Choi and Roh 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Chl is a negative effect of UV-B and may be an indication of ongoing senescence (Weichmann 2000). Many reports have shown that one of the most common symptoms of elevated UV-B exposure is a decrease in Chl concentration (Medina et al 2010, Zu et al 2011. Declines in Chl concentration in UV-B treated shoots have been related to the suppression of aminolevulinic acid synthesis or a reduction in protochlorophyllide (Choi and Roh 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These seasonal variations in k PAR following the annual succession of phytoplankton were also determined in the Lake Cacique Chiquichano (Chubut Province) in the Patagonian Plateau, where k PAR values varied between 0.44 and 12.5 m -1 (Gonçalves et al 2007. Finally, in studies carried out in the Peri-Pampean Sierras (i.e., Lake La Angostura) Helbling et al (2006) determined values of k PAR of 1.7 m -1 during the summer, however, Medina et al (2010) found relatively higher penetration of solar radiation at the same study site, with 83-86% (PAR) of incoming irradiances at 0.30 m. These differences are attributed to the fact that the former study was performed during the rainy season thus higher amounts of terrigenous material were transported to the lake.…”
Section: Solar Radiation and The Underwater Light Climatementioning
confidence: 72%